Risk of stent thrombosis among bare-metal stents, first-generation drug-eluting stents, and second-generation drug-eluting stents: Results from a registry of 18,334 patients - Tada, Tomohisa; Byrne, Robert A.; Simunovic, Iva; King, Lamin A.; Cassese, Salvatore; Joner, Michael; Fusaro, Massimiliano; Schneider, Simon; Schulz, Stefanie; Ibrahim, Tareq; Ott, Ilka; Massberg, Steffen; et al. (Jacc-Cardiovascular Interventions, 2013)
Objectives This study sought to compare the risk of stent thrombosis among patients treated with bare-metal stents (BMS), first-generation drug-eluting stents (G1-DES), and second-generation drug-eluting stents (G2-DES) for a period of 3 years. Background In patients undergoing coronary stenting, there is a scarcity of long-term follow-up data on cohorts large enough to compare rates of stent thrombosis across the stent generations. Methods A total of 18,334 patients undergoing successful coronary stent implantation from 1998 to 2011 at 2 centers in Munich, Germany, were included in this study. Patients were stratified into 3 groups according to treatment with BMS, G1-DES, and G2-DES. Results The cumulative incidence of definite stent thrombosis at 3 years was 1.5% with BMS, 2.2% with G1-DES, and 1.0% with G2-DES. On multivariate analysis, G1-DES compared with BMS showed a significantly higher risk of stent thrombosis (odds ratio [OR]: 2.05; 95% confidence interval [CI]: 1.47 to 2.86; p < 0.001). G2-DES were associated with a similar risk of stent thrombosis compared with BMS (OR: 0.82; 95% CI: 0.56 to 1.19; p = 0.30). Beyond 1 year, the risk of stent thrombosis was significantly increased with G1-DES compared with BMS (OR: 4.72; 95% CI: 2.01 to 11.1; p < 0.001), but not with G2-DES compared with BMS (OR: 1.01; 95% CI: 0.32 to 3.25; p = 0.98). Conclusions In a large cohort of unselected patients undergoing coronary stenting, compared with BMS, there was a significant excess risk of stent thrombosis at 3 years with G1-DES, driven by an increased risk of stent thrombosis events beyond 1 year. G2-DES were associated with a similar risk of stent thrombosis compared with BMS. © 2013 BY THE AMERICAN COLLEGE OF CARDIOLOGY FOUNDATION PUBLISHED BY ELSEVIER INC.
CRIS-Team Scopus Importer:2023-03-08
Keywords: bare-metal stent(s); drug-eluting stent(s); stent thrombosis